Maslahah and its Application in Islamic Finance - Mohd Zameri, Sarah Nursaadah; Syed Alwi, Sharifah Faigah; Mohammad Hatta, Mohammad Firdaus; Saiful Fikri, Aula Ahmad Hafidh (UUM PRESS, 2024)
In light of the complexity of contemporary Islamic banking and finance difficulties and the fact that certain answers cannot be found in traditional legal texts, maslahah or the public interest has emerged as a secondary source of Shariah to address these difficulties and issues. Maslahah which embodies the notion of achieving the public interest and preventing harm, has been crucial to the development and evolution of products and services in Islamic finance. The purpose of this study is to analyze the concept of maslahah as the secondary source of Shariah whereby the definition, classification, validity of maslahah and the conditions of validity are discussed. The study also highlighted its applications in Islamic finance products and services besides conducting library research analysis on literature from both classical and contemporary maslahah literature as well as the current application of maslahah in Islamic finance products and services. The study explained maslahah mu’tabarah, maslahah mulgha, and maslahah mursalah as the three classifications of maslahah which are considered valid when they are genuine (haqiqiyyah), general (kulliyah) and not in conflict with clear Quranic verse according to the Muslim jurists. The study also found that the concept of maslahah is applied in the establishment of Islamic banking and finance institutions as83 well as the Islamic capital market whereby policies were developed by the government for the Islamic banking institutions to ensure the products are Shariah-compliant. Additional collateral is required, based on the principles of usul fiqh, for the renewal of mudarabah transactions. On the other hand, ta’widh and gharamah are introduced by Islamic banks to safeguard the interests of both banks and the customers. Finally, zakat financing can help entrepreneurs repay their existing financial obligations.